Modality and subjetivity: notions to review - Soler Bonafont, M. Amparo (Boletín de Filología, 2023)
This paper reviews the concepts of modality and subjectivity, according to different bibliographic studies. The main purpose of the review is to note the defining flaws of both domains, which cause confusion when it comes to being explained in the uses of different linguistic units (from verbs to adverbs and discursive particles). The approximation carried out shows that the description of both concepts is intertwined from the beginning of the theorizing about it, but, above all, that its descriptive features are eminently semantic, although the grammatical (and functional) categories that mainly manifest these phenomena operate at the pragmatic level. Thus, here we propose new definitions of modality and subjectivity that they are not mutually exclusive nor overshadow either of the two domains. For this purpose, it is proposed a conception of the studied terms based in some definition of last year’s cognitive-functional theories (Nuyts and Van der Auwera 2016, Abraham 2020).